2015
DOI: 10.1186/s12906-015-0897-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of herbal medicines and their trapping abilities against methylglyoxal-derived advanced glycation end-products

Abstract: BackgroundMethylglyoxal (MG) is one of the most reactive glycating agents, which result the formation of advanced glycation end-products (AGEs) that have been implicated in the progression of age-related diseases. Inhibition of MG-induced AGE formation is the imperative approach for alleviating diabetic complications. The objective of this study was to investigate the MG-trapping abilities of herbal medicines and their inhibitory activities on the formation of MG-derived AGEs.MethodsThe aqueous extract of herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The total phenolic content (TPC) of extracts was previously reported by our experiments [15] that have been used for the calculation of Pearson’s correlation coefficients in the present study. The Pearson’s correlation coefficients between the variables are presented in Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total phenolic content (TPC) of extracts was previously reported by our experiments [15] that have been used for the calculation of Pearson’s correlation coefficients in the present study. The Pearson’s correlation coefficients between the variables are presented in Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The plant authentication was performed according to our previous report [15]. The extraction of herbal medicines was done according to a previous report [15]. Briefly, the plants (20 g) were boiled in distilled water (800 mL) for 3 h at 95 °C before filtered through Whatman No.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many natural products, including the extracts of herbal plants, mung beans, peanuts, or natural compounds, such as quercetin and myricitrin, have been reported to inhibit the formation of AGEs induced by MGO [21,[32][33][34][35]. Moreover, it has been reported that natural products block the MGO-induced AGE formation through the trapping of MGO [21,32]. This MGO trapping mechanism by flavonoids from natural products involves the trapping of the reactive dicarbonyl MGO species at the two unsubstituted positions 6 and 8 in the A-ring, the major active sites of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these exhibited antidiabetic activity in previous studies. They have also been reported to possess other pharmacological effects, such as antimicrobial, 24,25) antiviral, 26) anticancer, 27) anti-inflammatory, 28,29) antipyretic, 29) analgesic, 29) antioxidant, 30) antihemolytic, 31) immunomodulatory, 32) antiallergic, 33) neuroprotective, 34,35) antiglycation, 36) and antiobesity 37) activities (Table 2).…”
Section: Naphthoquinones Containing Plants In Thailandmentioning
confidence: 99%